Gpbar1-mediated SIRT1-PGC-1α axis maintains mitochondrial homeostasis and mitigates renal injury in obstructive jaundice - Mingchen Li; Kai Luo; Xu Sun; Yuting Zhao; Haiyang Chen; Courtney Quan; Caiming Xu; Guixin Zhang (Scientific Reports)
Abstract Obstructive jaundice (OJ)-induced kidney injury has a high mortality rate, severely affecting patient prognosis. Gpbar1, a bile acid receptor, plays a key role in maintaining tissue homeostasis in organs such as the liver and pancreas during OJ. However, its role in obstructive jaundice-induced kidney injury remains unexplored. This study investigated the protective role of Gpbar1 in OJ-induced kidney injury. Sprague-Dawley rats underwent common bile duct ligation to establish an OJ model. Organ damage was evaluated by pathological examination, TUNEL staining, and liver/kidney function tests to assess both OJ model establishment and kidney injury. Mitochondrial function changes were assessed through electron microscopy, SOD, MDA, GSH and ATP detection. Immunohistochemistry and Western blot were used to assess Gpbar1, SIRT1, and PGC-1α expression. HK-2 cells were treated with deoxycholic acid to establish a renal tubular epithelial cell injury model. Lentiviral vectors were used to overexpress or knock down Gpbar1, combined with interventions using SIRT1 and PGC-1α agonists and inhibitors. The Gpbar1-SIRT1-PGC-1α axis was validated by qRT-PCR and WB. The protective role of the Gpbar1-SIRT1-PGC-1α axis in OJ-induced kidney injury was studied using CCK-8, transmission electron microscopy, ROS detection, and mitochondrial membrane potential assays. In the rat OJ model, the model group exhibited injury-related pathological changes compared to control group. Liver and kidney function markers and TUNEL-positive cells significantly increased, and structural and functional damage in the kidneys occurred. Mitochondrial structural disorder occurred in the kidneys, with significant reductions in SOD, GSH, and ATP levels, while MDA levels were significantly increased, indicating impaired antioxidant capacity and energy metabolism dysfunction. IHC, WB, and qRT-PCR revealed that protein and mRNA levels of Gpbar1, SIRT1, and PGC-1α in kidney tissues were lower in the model group. In the cellular model, DCA treatment and Gpbar1 knockdown significantly reduced cell viability, caused mitochondrial structural disorder, increased ROS levels and decreased JC-1 ratio, while Gpbar1 overexpression reversed these changes. After treatment with the SIRT1 inhibitor EX527, PGC-1α expression significantly decreased. We used SIRT1 inhibitors, activators and PGC-1α inhibitors to conduct positive and negative regulation experiments and confirmed the hierarchical regulatory effect of Gpbar1 on SIRT1-PGC-1α. Gpbar1 influences oxidative stress resistance via the SIRT1-PGC-1α axis, promotes mitochondrial functional homeostasis, and alleviates kidney injury induced by obstructive jaundice.